Behavioral Risk Factors of HBV Infection and its Association with HBs Ag Positivity among Residents of Kaza Sub- division of District Lahaul & Spiti in Himachal Pradesh - Gupta, Anmol; Sachdeva, Amit; Sharma, Rajesh; Sharma, Neetu; Barall, Deepesh; Bodh, Vishal; Sharma, Dikshant; Sharma, Brij (Indian Journal of Community Health, 2023)
Background: Chronic viral hepatitis is a major global public health problem, an important cause of morbidity and mortality. We conducted this study to evaluate the behavioral risk factors of HBV infection and its association with HBsAg positivity among residents of Kaza sub-division of district Lahaul & Spiti in Himachal Pradesh. Material & Methods: The study was carried out by the Gastroenterology, Community Medicine, and Microbiology Department at Indira Gandhi Medical College Shimla at Kaza, a subdivision of Lahaul & Spiti. The cluster sampling technique was used to get the desired sample size of 4000. Forty clusters were chosen using a probability proportionate to size sampling method, and 100 research participants were added to each cluster using a simple random sampling method. The data was gathered using a pre-tested interview plan. A blood sample of 5ml from each study participant was obtained, and its HBsAg content was examined. Results: In our study, 2.7% of the interviewed respondents’ parents were positive for hepatitis B and 3.7% reported one positive family member. Injectable drug use was reported by 1.6 (68/4231). Among these users 8.8% (6/68) shared needles with other IDUs in last 12 months and 35.3% (24/68) used a common container to draw up drug solution. Sexual intercourse was reported to be experienced by 15.5 (655/4231) and 12.2% either did not disclose or were children. Out of those who ever experienced sexual/penetrative intercourse 38.3% (251/655) had reported it with someone else other than a spouse. Majority of these had two partners other than a spouse (30.3%; 76/251). Around 30% (195/655) reported of using a condom in their last intercourse. Body piercings or a tattoo from someone who doesn’t sterilize his or her equipment, including local treatment from lamas, was prevalent among 16.3% of the population (689/4231). Acupuncture was taken as a remedy for any medical condition by 9% of participants. Regression analysis also revealed that one infected family member emerged as an independent factor associated with HBsAg positive test after adjusting for confounders. Conclusion: Our study provided much important information concerning hepatitis B risk factors in this tribal group. Health education about behavioral risk factors among this tribal population should be the main intervention that might help limit the spread of these blood-borne infections.